Empirical investigation of Malaysian curators’ perspectives on digital storytelling process and elements for museum exhibition guideline / Hafizah Rosli - Rosli, Hafizah (2023)
The museum is considered as a place that embraces the valorisation of stories both in visual display and narrative. Towards this, a digital storytelling (DST) is a technology that combines the art of telling story using multimedia elements in order to create unique understanding and quality of experience. Successively, the trend from international studies on cultural heritage and museum studies established that DST is the most applicable exhibition presentation technique that transformed the way museum visitors think and learn and further reshape visitors’ judgement and experience. Across this scenario, however, museum studies trends in Malaysia indicate limited study on DST in museum exhibition that has been attributed to a knowledge gap in the practise of museum exhibitions process and element of DST in Malaysia. Due to this gap, this research aim to investigate the curators’ understanding level of DST process and elements in order to develop a practical guideline for museum exhibition across Malaysia practise. This qualitative exploratory case study project utilising museum curators as a sample group, driven by interpretivism research philosophies and an inductive approach across a mono-method utilising triangulation data through contextual document analysis, content analysis, semi-structured in-depth interviews with curators and thematic analysis. The main findings of this research established the most common elements and process among scholars, the level of understanding on DST process and element among Malaysian curators' and proposing an extended set of practical process and elements guidelines of DST to aid curators in designing museum exhibition multimedia or digital content from the Malaysian curators' perspective.